Little Bunny finds Christmas - Vainio, Pirkko (North-South ; Publishers Group UK [distributor], 2008)
Little Bunny and a group of other forest animals search for Christmas-- as bright as a shining star, as perfect as peace on Earth, and as sweet as a mother's love.